Room to Manoeuvre for Member States: Issues for Decision on the Occasion of the Transposition of the Damages Directive - Anna Piszcz (Market and Competition Law Review)
Soon Member States will bring into force the laws, regulations and administrative provisions necessary to comply with the Damages Directive (2014/104/EU). Usually Member States do not seem willing to introduce a broader scope of the application of principles embodied in EU directives. For Member States, “copy-pasting” a directive's content into a piece of national legislation is one of the simplest ways to implement a directive (another very simple one is implementation by reference; it is just referring the reader to the directive and should not be applied where the rules in a directive are not sufficiently precise, so it is not applied very often). Member States that work on the implementation of the Damages Directive either do it in a minimalist manner, mainly "copy-pasting" its content, or take the legislative opportunity to do something more and "tidy up" domestic provisions on the occasion of the transposition of the Directive. Some Member States have chosen that last option. The article attempts to highlight some of the considerations that may be of particular relevance in this process, with the aim of formulating some recommendations for national legislatures, even though implementation works are drawing to a dose. First, some “spontaneous harmonisation” of a scope broader than that provided for in the Directive is recommended on the background of the material (substantive) scope of the Directive and its transposition. The other important considerations are addressed to the personal scope of the Directive and its transposition. Finally, the short review of some more detailed issues for decision on the occasion of the transposition of the Directive is offered. Considerations regarding the principle of civil liability, the use of collective redress mechanisms, minimum harmonisation clauses, institutional design of private enforcement of competition law, as well as incentives to voluntarily provide compensation to injured parties can be found therein.